2021
DOI: 10.21203/rs.3.rs-815289/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors that impact acceptance of COVID-19 vaccination in different community-dwelling populations in China

Abstract: Background It is important to improve vaccination strategies and immunization programs to achieve herd immunity to infectious diseases, particularly in general community-dwelling populations. Methods To assess the acceptance of COVID-19 vaccination, we conducted face-to-face surveys and online surveys in Shanghai, Zhejiang, and Qinghai province. A fixed effects model and a random effects model were used to analyze factors associated with acceptance of COVID-19 vaccination. Findings The results indicated tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Due to different vaccination policies in different regions, the COVID-19 vaccination situation varies from region to region. An increasing number of studies have shown that there is a correlation between the prevalence of COVID-19 vaccination in different provinces in China and people's willingness to be vaccinated (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), but the willingness of residents to be vaccinated is not consistent across regions, which may be due to complex sociodemographics. Based on this, this study mainly conducted a meta-analysis on the associated factors of willingness to get COVID-19 vaccination in available studies, in order to evaluate the associated factors affecting people's willingness to vaccinate against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Due to different vaccination policies in different regions, the COVID-19 vaccination situation varies from region to region. An increasing number of studies have shown that there is a correlation between the prevalence of COVID-19 vaccination in different provinces in China and people's willingness to be vaccinated (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), but the willingness of residents to be vaccinated is not consistent across regions, which may be due to complex sociodemographics. Based on this, this study mainly conducted a meta-analysis on the associated factors of willingness to get COVID-19 vaccination in available studies, in order to evaluate the associated factors affecting people's willingness to vaccinate against COVID-19.…”
Section: Introductionmentioning
confidence: 99%